ANALYSIS OF PHYSICAL PRINCIPLES AND ACCURACY FACTORS IN THERMOPILE-BASED INFRARED THERMOMETERS FOR ELECTROMEDICAL APPLICATIONS - Gita cahyani (PULSE — Journal of Energy, Informatics & Biomedicine, 2026)
Infrared thermometers have become widely used in medical applications due to their ability to perform rapid, non-contact body temperature measurements while minimizing the risk of cross-contamination. This paper reviews the fundamental physical principles and electronic systems underlying the operation of infrared thermometers in electromedical applications. The discussion covers electromagnetic radiation, blackbody radiation, the Stefan–Boltzmann law, Wien’s displacement law, and the Seebeck effect, which forms the basis of thermopile sensor operation. Furthermore, the signal acquisition process, including optical focusing, low-noise amplification, analog-to-digital conversion, and microprocessor-based temperature estimation, is described to explain the complete measurement mechanism. The review also examines key factors affecting measurement accuracy, including emissivity, ambient temperature, measurement distance, sensor noise, and analog-to-digital converter resolution. Understanding the interaction between these physical phenomena and electronic subsystems is essential for improving the performance, reliability, and accuracy of infrared thermometers in clinical practice. This review provides a comprehensive reference for students, researchers, and practitioners in electromedical engineering to better understand the working principles and performance characteristics of non-contact infrared thermometers